Regulatory Lymphoid and Myeloid Cells Determine the Cardiac Immunopathogenesis of Trypanosoma cruzi Infection - Fresno, Manuel; Gironès, Núria (Frontiers in Microbiology, 2018)
Chagas disease is a multisystemic disorder caused by the protozoan parasite Trypanosoma cruzi, which affects approximately 8 million people in Latin America, killing 7000 people annually. Chagas disease is one of the main causes of death in the endemic area and the leading cause of infectious myocarditis in the world. T. cruzi infection induces 2 phases, acute and chronic, where the infection is initially asymptomatic and the majority of patients will remain clinically indeterminate for life. However, over a period of 10–30 years, approximately 30% of infected individuals will develop irreversible, potentially fatal cardiac syndromes (chronic chagasic cardiomyopathy [CCM]) and/or dilatation of the gastro-intestinal tract (megacolon or megaesophagus). Myocarditis is the most serious and frequent manifestation of chronic Chagas heart disease and appears in about 30% of infected individuals several years after infection occurs. Myocarditis is characterized by a mononuclear cell infiltrate that includes different types of myeloid and lymphoid cells and it can occur also in the acute phase. T. cruzi infects and replicates in macrophages and cardiomyocytes as well as in other nucleated cells. The pathogenesis of the chronic phase is thought to be dependent on an immune-inflammatory reaction to a low-grade replicative infection. It is known that cytokines produced by type 1 helper CD4+ T cells are able to control infection. However, the role that infiltrating lymphoid and myeloid cells may play in experimental and natural Chagas disease pathogenesis has not been completely elucidated, and several reports indicate that it depends on the mouse genetic background and parasite strain and/or inoculum. Here, we review the role that T cell CD4+ subsets, myeloid subclasses including myeloid-derived suppressor cells may play in the immunopathogenesis of Chagas disease with special focus on myocarditis, by comparing results obtained with different experimental animal models.